Pendidikan Nilai-Nilai Kebangsaan Di Pesantren : Riset di Pesantren Ashidiqiyah Jakarta Barat - Ali Mursyid (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2018)
In addition to transferring knowledge, education is the way to cultivate the values, such as civic values. Recently, the urgency of civic education is deemed important regarding the emergence of national crisis (the lack of civic and public values). Therefore, civic values must be implemented in educational institution such as pesantren. This paper is research summary on education values in Ashidiqiyah Pesantren Kedoya South Jakarta. The result inferred that civic education was cultivated in the Pesantren, including the personal character and nation character building. Personal character encompasses honesty, truthfulness, love to knowledge, sincerity, patient, self-restraint and others values of piety. While civic character constitutes tolerance, equality, and national unity and others. Civic values educated in the Pesantren are referenced to the Qur‟an, hadith and classical Islamic works (yellow book) and implemented through two systems: education (ta‟lim) and care systems. Ta‟lim system is implemented in formal education (madrasah) surrounding the Pesantren, starting from the lowest level (ibtidaiyyah) to the higher level Madrasah (aliyah) and Ma‟had Ali (as university). Ta‟lim system is also conducted through routine studies on Yellow Book and discussion forum (bahsul masa‟il), and the like. While care system tends to emphasize the habitual (ta‟dib). By the care, control and discipline systems, santri as subject of education is accustomed to practice the higher values of Islam, including civic values and self-defend to the bad values which polluted the civic values.